2022
DOI: 10.2186/jpr.jpr_d_22_00166
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and surface properties of additive manufactured zirconia under the different building directions

Abstract: The clinical application of dental prostheses manufactured using dental computer-aided design/computer-aided manufacturing (CAD/CAM) systems is now common, owing to the advances in digitalization in the field of dentistry [1]. A CAD/CAM system includes the processes of designing a dental prosthesis using CAD software, converting the scanned data into machining data using CAM software, and using either subtractive manufacturing (SM) or additive manufacturing (AM) technologies to fabricate the dental prosthesis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…In addition to 3D printed resin composites, ceramics and zirconia have also been tested [ 28 , 34 , 35 , 36 , 38 , 47 , 53 , 54 , 55 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to 3D printed resin composites, ceramics and zirconia have also been tested [ 28 , 34 , 35 , 36 , 38 , 47 , 53 , 54 , 55 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, crowns fabricated with both techniques could withstand 5 years of clinical service in the oral cavity. Miura et al investigated the mechanical properties of additively manufactured zirconia in two different studies [ 53 , 54 ]. They found that flexural strength is correlated with the printing angle.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The future prospects for prosthetic research in dental materials science are exciting and hold the potential to significantly improve the lives of individuals with dental prostheses. By developing more durable and biocompatible materials using 3D printing technology, artificial intelligence, and advanced regenerative medicine, researchers are poised to make great strides in this field [9,10]. By investing in dental materials science research, we can improve the quality of life of patients.…”
mentioning
confidence: 99%